Discussing terrorism: a pupil-inspired guide to UK counter-terrorism policy implementation in religious education classrooms in England. Issue 1 (2nd January 2016) - Quartermaine, Angela
Abstract : My research into pupils' perceptions of terrorism and current UK counter-terrorism policy highlights the need for more detailed and accurate discussions about the implementation of the educational aims, in particular those laid out by the Prevent Strategy. Religious education (RE) in England is affected by these aims, specifically the challenging of terrorist ideologies and improving community cohesion, but many RE teachers feel ill-equipped in dealing with the issues that might arise from terrorism discussions. Therefore, I suggest that clarification could help alleviate some of the teacher's concerns and help provide routes by which critical RE teaching and learning can take place.